MEKANISME CORPORATE GOVERNANCE DAN KEMUNGKINAN KECURANGAN DALAM PELAPORAN KEUANGAN - Satrio Wicaksono, Gregorius; Chariri, Anis (Diponegoro Journal of Accounting, 2015)
This study aims to obtain empirical evidence and to analyze the effect of corporate governance’s mechanism such as board size of commissioners, board composition of independent commissioners, audit committee, and internal audit effectiveness on likelihood of fraudulent financial reporting. Company size and leverage used as control variables in this study.The population in this study was non-financial companies listed on the Indonesia Stock Exchange in 2008 to 2012. Total sample used in this study was 38 companies, consist of 19 companies which did fraudulent financial reporting, and 19 companies which didn’t fraudulent financial reporting as matched companies by the criteria on the same of industry and total asset. Data analysis was performed with the descriptive statistic analysis, multikolonieritas test, and hypothesis test with logistic regression analysis.The results of analysis this study indicate that audit committee and internal audit effectiveness in a significant negative effect on likelihood of fraudulent financial reporting, while board size of commissioners and board composition of independent commissioners have no significant effect on likelihood of fraudulent financial reporting.